1982
DOI: 10.1002/jcp.1041130216
|View full text |Cite
|
Sign up to set email alerts
|

An early mitosis‐determining event in regenerating rat liver and its possible mediation by prostaglandins or thromboxane

Abstract: Inhibitors of prostaglandin and thromboxane production such as mefenamic acid, hydrocortisone, and dexamethasone prevented a large proportion of the parenchymal cells of rat liver, proliferatively activated by a two-thirds partial hepatectomy, from entering mitosis without preventing them from initiating or completing DNA synthesis. This specific mitosis-inhibiting action was maximum when the drugs were present during the first few hours after partial hepatectomy. In contrast, indomethacin, another inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 24 publications
(35 reference statements)
3
16
0
1
Order By: Relevance
“…Glucocorticoids are known to modulate the proliferation and maturation of various cell types (Guerriero and Florini, 1980;Rixon and Whitfield, 1982). In line with those observations, we have found that the continuous presence of dexamethasone either enhances or reduces the replicative activity of suckling rat hepatocytes de- Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Glucocorticoids are known to modulate the proliferation and maturation of various cell types (Guerriero and Florini, 1980;Rixon and Whitfield, 1982). In line with those observations, we have found that the continuous presence of dexamethasone either enhances or reduces the replicative activity of suckling rat hepatocytes de- Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Two notable groups of agents found to enhance growth responses in hepatocytes are prostaglandins (PGs) and adrenergic agonists. PGs have been implicated as promoters, or possibly triggers, of liver regeneration, based primarily on the finding that their levels D 1994 WILEY-LISS, INC. 0 1994 Wiley-Liss, Inc rise upon partial hepatectomy and that the proliferation can be blocked by cyclooxygenase inhibitors (Mac-Manus and Braceland, 1976;Miura and Fukui, 1979; Rixon and Whitfield, 1982;Callery et al, 1991). Several PGs, including PGE, and PGF,,, enhance DNA synthesis in neonatal and adult hepatocytes in vitro (Andreis et al, 1981;Armato and Andreis, 1983;Skouteris et al, 1988;Skouteris and Kaser, 1991;Skouteris and McMenamin, 19921, and some of these data have also been taken to suggest that PGs play a role as mediators of mitogenic effects of EGF and TGFa in hepatocytes (Skouteris et al, 1988;Skouteris and Kaser, 1991;Skouteris and McMenamin, 1992).…”
mentioning
confidence: 99%
“…But these events are not parts of the preparations for chromosome replication. Instead, the prostaglandins (or thromboxane) and cyclic AMP separately stimulate two independent processes around 2 and 3 hours after HPX that combine to enable the cells to transit the G 2 phase and enter mitosis many hours later, after they have finished replicating their chromosomes [92,93]. It is interesting to note that certain cyclic AMP-triggered prereplicative events (spindle plaque body duplication) in the yeast S. cerevisiae are also concerned with mitosis rather than chromosome replication [94,95] (Fig.…”
mentioning
confidence: 99%